418PLessons learnt from treatment of foot sarcomas: Analysis from dedicated sarcoma clinic in North India. (24th November 2019) - Pawar, S J; Rastogi, S; Dhamija, E; Barwad, A; Kumar, V; Pandey, R; Shishak, S; Kalra, K; Aggarwal, A; Garg, A; Mridha, A R; Chaubey, J; et al.
Abstract: Background: There is sparse data available on foot sarcomas treated on contemporary protocols. Methods: This retrospective analysis involved 27 cases of foot sarcomas managed with multi-modality treatment under Sarcoma Clinic, at tertiary care hospital between January 2014 to May 2019. Baseline demographics, radiographic tumour characteristics, histological diagnosis, type of treatment received and oncological outcomes were noted for all cases. Statistical analysis was done by STATA version 13.0. Survival curves were analyzed by Kaplan Meir test and univariate analysis was done by Log Rank test. Results: Median age was 26 years (range: 20 – 46 years). Median duration of symptoms were 11 months (Range: 5 – 24 months). Radiologically mean largest diameter of tumour was 6.5 cm (CI: 1.1 – 12 cm). Seven tumours (26%) arose from bone and 20 form soft tissue (74%). In tumours arising from bone, metatarsal was most commonly site of involvement (3 out of 7). Most common histology was synovial sarcoma (44%) f/b Ewing's sarcoma (26%) f/b others (RMS, DFSP, MPNST, angiosarcoma). Ten patients (37%) had metastatic disease at presentation, lung being most common site (80%). Histological discordance with review diagnosis was seen in 50 % cases. Amputation was needed in 10 cases (37%) (palliative - 5, curative - 5) while limb salvage surgery was done in 10 (all curative). Adjuvant radiation was given in 7 out of 10 cases (70%). At last follow up 16 out of 27 patients (60%) were alive without disease, 4 (11%) with disease while 8 (29%) have died. With median follow-up of 43 months (Range 8 - 63 months) median PFS was 22 months. Median PFS in non-metastatic group was 48 months, while in metastatic group it was 8 months. On univariate analysis, median OS was significantly different between metastatic vs non-metastatic group (HR 10.93, p = 0.03). Conclusions: Foot sarcomas happen in young adults irrespective of pathology with synovial sarcoma and Ewing's sarcoma being most common histologies. Amputation rates are quite high even considering small size, owing to anatomy of the region as noted in previous studies. The treatment required for non metastatic disease is multimodality including use of radiation. If treated in multidisciplinary clinic outcomes can certainly be improved. Legal entity responsible for the study: Sameer Rastogi. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.